Huma Betang: Identitas Moral Kultural Suku Dayak Ngaju Kalimantan Tengah - Apandie, Chris; Ar, Endang Danial (Journal of Moral and Civic Education, 2019)
Nowadays local and national cultures are gradually left behind. Cultural artifacts—while having beyond-physical meaning, even moral and cultural identities—are no longer maintained neither have philosophical attraction. Exploration of philosophical values ​​in huma betang can be a step to revitalize culture in order to strengthen Indonesians’ cultural moral identity. Huma Betang is commonly known as "the big house". Dayak people—a traditional ethnic group in Borneo—with diverse religions and beliefs have been inhabiting the houses for a long time in harmony and peace. This research used qualitative approach with ethnographic method. Research was located in Betang Toyoi Tumbang Malahoi, Rungan District, Gunung Mas Regency, Central Borneo province. For the Dayak people, huma betang is more than just a place to live; it is the center of Dayak's life structure. Cultural identities reflected are that huma bentang: 1) as a reflection of tolerance; 2) as the origin of unity and togetherness among Dayak people after the Tumbang Anoi peace agreement; 3) as a replica of communal system adopted by Dayak people; 4) contains cosmological patterns that reflect a balance of values; 5) as a reflection of democratic and egalitarian life; 6) through the pattern of life in it delivers the concept of Dayak’s leadership; 7) represents the collective principle; 8) as the ideal model of a pluralist community system. Keywords: huma betang, cultural morality identity, Dayak ethnic group, Central Kalimantan ABSTRAK Dewasa ini benda cagar budaya seolah tidak lagi memiliki daya tarik filosofis dan tidak terpelihara, padahal benda cagar alam mengandung pemaknaan yang lebih dari sekedar fisik, bahkan merupakan identitas moral kultural. Eksplorasi nilai filosofis pada huma betang dapat menjadi langkah revitalisasi kebudayaan guna memperkuat identitas moral kultural warga negara Indonesia. Huma Betang dikenal secara luas dengan istilah “rumah besar”. Rumah ini ditinggali orang Dayak sejak jaman dulu dengan beragam agama dan kepercayaan di dalamnya, namun penghuninya tetap hidup berdampingan. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi. Lokasi penelitian adalah di Betang Toyoi Tumbang Malahoi Kecamatan Rungan Kabupaten Gunung Mas Kalimantan Tengah. Bagi masyarakat Suku Dayak huma betang tidak hanya sekedar tempat tinggal, tapi merupakan jantung dari struktur kehidupan orang Dayak. Identitas kultural yang terefleksi yaitu huma bentang: 1) sebagai refleksi kehidupan masyarakat yang toleran; 2) sebagai asal mula tumbuhnya rasa persatuan dan kebersamaan antar suku Dayak setelah kesepakatan damai Tumbang Anoi; 3) sebagai replika sistem komunal yang dianut masyarakat Suku Dayak; 4) mengandung pola kosmologi yang mencerminkan keseimbangan sebuah nilai; 5) sebagai cerminan kehidupan demokratis dan egaliter; 6) melalui pola kehidupan melahirkan konsep kepemimpinan Suku Dayak; 7) merepresentasikan prinsip kolektif; 8) sebagai model ideal sistem masyarakat pluralis. Kata kunci: huma betang, identitas moral kultural, suku Dayak, Kalimantan Tengah